(untitled) (Research, Society and Development, 2023)
The HPV vaccine is currently the best way to prevent cervical cancer. Through a retrospective study, this work aimed to collect data on the distribution of vaccines against HPV in Brazil, evaluating the percentage of doses distributed, since the country has committed itself to the World Health Organization (WHO) to reach the global goal 90% vaccination coverage of girls before the age of 15 by 2030. The data were obtained using the TabNet algorithm developed by DATASUS and the results showed that the number of immunizations against HPV was higher in the years 2014 and 2015, with 7,874 .743 and 5,774,727 doses distributed respectively, and less in 2022 with 2,050,724 doses. In the analysis by applied doses, between 2014 and 2022 there was a 73.90% reduction in the number of doses, in addition the distribution of the vaccine was smaller for the 2nd dose both in the year 2014 and in the year 2022. Although it is scientifically proven that vaccine against HPV is extremely relevant for the reduction in the number of cases of CC in primary prevention, the findings of this study point to a considerable reduction in the demand for this vaccine over the last nine years. The impact of Fake news would be one of those responsible for the decrease in the number of immunizations in the country, aggravated by the interruption of vaccination during the COVID-19 Pandemic. It is urgent for Brazil to use more effective strategies to achieve the global goal of immunizations.